"Beautiful Dream" or "Loathsome Delusion": Imagination and Ideality in Nineteenth-Century Denmark. Issue 1 (2nd January 2018) - Kallenbach, Ulla
ABSTRACT: This article examines the concept of imagination and its relation to ideality in a Danish theater context from the early nineteenth century to the late 1860s. The theater is at times a problematic arena where the ideal by way of the imagination embodies, encounters, and faces up to reality. From the veneration of the divine imagination, exemplified by the poet Adam Oehlenschläger (1779–1850) over the aesthetic idealism of the philosopher F. C. Sibbern (1785–1872) and the refined idealism of poet and critic Johan Ludvig Heiberg (1791–1860), to the problematization of imagination and ideality in the works of Søren Kierkegaard (1813–55) and actress Johanne Luise Heiberg (1812–90), this article uncovers a broad range of shifting interpretations of the relation of imagination to ideality. Using the perspective of the theater as a prism for analyzing this relationship offers a nuanced insight not only into Danish interpretations of imagination and ideality, but also into the appraisal of the theater itself and the art of acting.